Polyphenolic Characterisation of Vranac, Kratosija and Cabernet Sauvignon (Vitis vinifera L. cv.) Grapes and Wines from Different Vineyard Locations in Montenegro - Pajovic, R.; Raicevic, D.; Popovic, T.; Sivilotti, P.; Lisjak, K.; Vanzo, A. (South African Journal of Enology and Viticulture, 2016)
In Montenegro, red wines are produced predominantly, and Vranac accounts for nearly 80% of these wines, followed by Kratosija and Cabernet Sauvignon. In order to characterise polyphenols in red varieties, grapes were sampled from representative vineyards at harvest time during 2011 and 2012. The content and distribution of extractable anthocyanins, low-molecular mass proanthocyanidins (LMP) and highmolecular mass proanthocyanidins (HMP) in the seeds and skins of the grape berries were evaluated by applying a five-day extraction method using ethanol:water (12:88) as extraction solvent. On average, the highest content of LMP (2 006 and 1 690 mg/kg of grape fresh mass in years 2011 and 2012 respectively), HMP (2 705 and 2 805 mg/kg in years 2011 and 2012 respectively) and anthocyanins (1 035 mg/kg in the year 2011) was found in the Cabernet Sauvignon grapes. The highest content of anthocyanins (1 113 mg/kg in the year 2012) and the lowest content of LMP (1 103 and 846 mg/kg in years 2011 and 2012 respectively) was found in Vranac grapes. Kratosija grapes had the lowest anthocyanin content (456 and 517 mg/kg in years 2011 and 2012 respectively), and levels of LMP were similar to Vranac. The percentage distributions of LMP between skins and seeds were 34:66, 39:61 and 49:51, whereas the distributions of HMP between skins and seeds were 67:33, 62:38 and 64:36 for Vranac, Kratosija and Cabernet Sauvignon respectively. All varieties had more LMP in the seeds and more HMP in the skins of the grapes. The results obtained are important to better understand the polyphenolic potential of Montenegrin red grape varieties.